Pembuatan Komposit Matrik Aluminium Diperkuat Silicon Carbida Dan Rice Husk Ash Dengan Metode Metalurgi Serbuk - Dylan, Arise Graafian; Sugiyarto, Sugiyarto; Wanto, Agus; Budi, Abdul; Sukanto, Sukanto (Universitas Nusa Cendana, 2023)
Brake lining components that contain asbestos are dangerous for human health, so innovation materials environmentally friendly is needed. This research aims to determine the effect of volume fraction and sintering temperature to density and hardness of recycled aluminum matrix composites, reinforced with silicon carbide and rice husk ash using the powder metallurgy method, with varying reinforcement volume fractions 10%, 15%, and 20%. The powder mixing process uses a mechanical alloying method, while the hot compaction process uses a two-way pressing method with a hydraulic pump machine compaction pressure of 6000 PSi. The sintering temperature was varied at 550°C, 580°C, 610°C. Density testing refers to Archimedes' law with the ASTM B 962-17 standard, while hardness testing uses Portable Brinel with the ASTM E110-14 standard. The density and hardness test results show that the value increases with the amount of matrix used. For samples volume fraction 90%, the highest density value is 1.72 g/cm3 and the highest hardness value is 40HB. Based on microstructural analysis, this condition occurs because the relatively low duration of the powder mechanical alloying process has resulted in agglomeration of the reinforcing powder, and the impact interlocking bond becomes lower with increasing reinforcing powder used.